2019
DOI: 10.1093/ofid/ofz337
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Predisposition Variants in Kaposi Sarcoma as Detected by Whole-Genome Sequencing

Abstract: Familial clustering of classic Kaposi sarcoma (CKS) is rare with, approximately 100 families reported to date. We studied 2 consanguineous families, 1 Iranian and 1 Israeli, with multiple cases of adult CKS and without overt underlying immunodeficiency. We performed genome-wide linkage analysis and whole-genome sequencing to discover the putative genetic cause for predisposition. A 9-kb homozygous intronic deletion in RP11-259O2.1 in the Iranian family and 2 homozygous variants, 1 in SCUBE2 and the other in CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous studies have identified CDHR5- SNPs located close to IRF7 31 , 32 and associated with systemic sclerosis (SS) 32 . The candidate gene CDHR5 is a member of the cadherin family which interacts with the β-catenin pathway 33 . These observations are in agreement with a growing body of evidence that highlights that genetic effects are largely context and time-specific, and implicates that future research and data collection of pathological and molecular status within longitudinal larger autoimmune populations will be able to decipher many more genetic variants with important regulatory functions in autoimmunity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified CDHR5- SNPs located close to IRF7 31 , 32 and associated with systemic sclerosis (SS) 32 . The candidate gene CDHR5 is a member of the cadherin family which interacts with the β-catenin pathway 33 . These observations are in agreement with a growing body of evidence that highlights that genetic effects are largely context and time-specific, and implicates that future research and data collection of pathological and molecular status within longitudinal larger autoimmune populations will be able to decipher many more genetic variants with important regulatory functions in autoimmunity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified CDHR5- SNPs located close to IRF7 (37,38) and associated with systemic sclerosis (SS) (38). The candidate gene CDHR5 is a member of the cadherin family which interacts with the β-catenin pathway (39). These observations are in agreement with agrowing body of evidence that highlights that genetic effects are largely context and time-specific, and implicates that future research and data collection of pathological and molecular status within longitudinal larger autoimmune populations will be able to decipher many more genetic variants with important regulatory functions in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%